EFMC: Trends in Medicinal Chemistry and Chemical Biology. (28th February 2023) - Auberson, Yves P.; Arimondo, Paola B.; Duca, Maria; Essig, Sebastian; Grether, Uwe; Rufer, Arne C.; Sbardella, Gianluca; Schopfer, Ulrich; Torrens, Antoni; van der Stelt, Mario; Vauzeilles, Boris; Vázquez, Olalla; et al.
Abstract: Ground‐breaking research in disease biology and continuous efforts in method development have uncovered a range of potential new drug targets. Increasingly, the drug discovery process is informed by technologies involving chemical probes as tools. Applications for chemical probes comprise target identification and assessment, as well as the qualification of small molecules as chemical starting points and drug candidates. Progress in probe chemistry has opened the way to novel assay formats and pharmaceutical compound classes. The European Federation of Medicinal Chemistry and Chemical Biology (EFMC) has launched the Chemical Biology Initiative to advance science in the field of medicinal chemistry and chemical biology, while representing all members of this extended scientific community. This review provides an overview of the many important developments in the field of chemical biology that have happened at the lively interface of academic and industrial research. Abstract : A wealth of opportunities : Novel tools for chemical biology including chemical inducers of proximity, designer probes or RNA‐targeting agents enable innovative tactics for therapeutic approaches. This article explores recent developments combining the power of medicinal chemistry and chemical biology, highlighting their extraordinary potential to address sophisticated biological questions and manipulate complex biological pathways to develop novel therapies.